Assessing the neural mechanisms of chronic knee osteoarthritis pain using functional magnetic resonance imaging - Cottam, William (2018)
Chronic pain is a multifactorial experience combining sensory, affective and cognitive components and the underlying neural activity related to pain is subsequently diverse and encompasses widespread regions of the brain. Functional neuroimaging studies have suggested altered patterns of brain activity relating to chronic pain and in response to acute experimental pain but these findings have been inconsistent. Furthermore, research into chronic knee osteoarthritis pain (one of the most commonly presenting chronic pain states) has to date been lacking. The research here seeks to first assess the consistency of findings within the present literature and subsequently use these findings to motivate investigation into the neural correlates of chronic pain and its impact on brain state using advanced functional magnetic resonance imaging techniques alongside questionnaire-based participant report in a chronic knee osteoarthritis pain cohort.